PERCEIVED ORGANIZATIONAL SUPPORT DAN PENGARUHNYA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN JOB SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Jawa Timur Park 1) - Lailiy Anisatul Maula; Tri Wulida Afrianty (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
The aim of this research is to analyze the influence of perceived organizational support (POS) on organizational citizenship behavior (OCB) mediated by job satisfaction. The respondents of this research were 174 employees of Jawa Timur Park 1. To test the hypotheses a hierarchical regression analysis was conducted using SPSS version 21. The result showed that 1) there was a positive effect of perceived organizational support on job satisfaction 2) there was a positive effect of perceived organizational support on organizational citizenship behavior 3) there was a positive effect of job satisfaction on organizational citizenship behavior. In addition, 4) job satisfaction was confirmed as a mediating variable on the effect of perceived organizational support on organizational citizenship behavior in Jawa Timur Park 1. Keywords: Perceived Organizational Support, Job Satisfaction, Organizational Citizenship Behavior. ABSTRAK Tujuan penelitian ini adalah untuk menganalisis pengaruh perceived organizational support (POS) terhadap organizational citizenship behavior (OCB) yang dimediasi oleh job satisfaction. Responden dalam penelitian ini adalah 174 karyawan Jawa Timur Park 1. Untuk menguji hipotesis menggunakan hierarchial regression analysis dengan bantuan SPSS versi 21. Hasil penelitian ini menunjukkan bahwa: 1) terdapat pengaruh positif perceived organizational support terhadap job satisfaction2) terdapat pengaruh positif perceived organizational support terhadap organizational citizenship behavior, 3) terdapat pengaruh positif job satisfaction terhadap organizational citizenship behavior. Selain itu 4) job satisfaction terbukti sebagai variabel mediasi pada pengaruh perceived organizational support terhadap organizational citizenship behavior di Jawa Timur Park 1. Kata Kunci: Perceived Organizational Support, Job Satisfaction, Organizational Citizenship Behavior.